Análise de genotoxicidade: otimização de método laboratorial e avaliação em recém-nascidos de mães com restrição de crescimento intrauterino exercitadas durante a prenhez - Oliveira Netto, Aline de [UNESP] (2013)
To contribute the knowledge of the diabetes effects during pregnancy in the DNA damage, we performed a literature review using two groups of keywords: 1) diabetes, DNA damage, pregnancy and 2) rat, diabetes, DNA damage, pregnancy, in site of the database of the National Center for Biotechnology Information (NCBI-PUBMED). In the first group of keywords were found 28 articles. In the second group, there were 13 articles, which 11 were equal to the first group. Then, 28 articles were analyzed. Of these articles, 28,28% were considered adequate for writing the review, while 71,42% were considered inappropriate because they presented no coherent titles and abstracts. Of these articles, 37.5% were related to human research, 50% in experimental animals and 12.5% in humans and animals. Thus, in general, the articles showed that diabetes increases the reactive oxygen species that causes nucleic acid damage and this exacerbates maternal, embryonic and fetal oxidative stress